The “LARI KALCER” Phenomenon And The Revival Of Micro, Small, And Medium Enterprises (Msmes) In The Arga Makmur Square Area - Metriko Haderian; Yenisrida Yenisrida; Muhammad Rahman Febliansa; Dodi Hardinata (Universitas Dehasen Bengkulu, 2026)
The phenomenon of the “KALCER” (Run Fast, Run; If Tired, Find Ice) running community has transformed Arga Makmur Square into a lively public space and a center for creative economy. This article analyzes the symbiotic relationship between running activities and the growth of Micro, Small, and Medium Enterprises (MSMEs) in the surrounding area. The research uses a qualitative approach with participatory observation and in-depth interviews. The results show that KALCER acts as a catalyst by providing a guaranteed and friendly market for MSMEs, especially in the culinary sector. Conversely, the presence of various MSMEs increases the attractiveness and recreational value of the running event. This symbiosis not only boosts local economic income but also revitalizes the social function of the town square as an inclusive and dynamic public space. This study concludes that collaboration between hobby communities and local MSMEs can be an effective model for circular economic development and the revitalization of public spaces in the region.